NON-ACCOUNTING STUDENTS’ PERCEPTIONS ON THE USEFULNESS OF GAMIFICATION IN SUPPORTING COGNITIVE DEVELOPMENT - Rosaline Tandiono; Valentina Tohang; Yanthi Hutagaol-Martowidjojo (Universitas Pendidikan Indonesia, 2022)
Main Purpose - This study aims to examine the usefulness of the gamification teaching method in assisting non-accounting students in understanding accounting courses.Method – The current study relies on forty non-accounting students’ perceptions as its qualitative empirical data which was collected through students’ self-reflection reports. Self-reflection is perceived to be the most appropriate medium for students to express their thought and feeling freely.Main Findings - The results show that the majority of the students favor gamification and the specifically designed game for accounting courses assists them in understanding accounting terms and concepts, and financial statements, and helps them in visualizing a real business environment. Several features of the game also assist in the students learning process, i.e., the repetitive quiz questions, direct feedback, and the game itself. Nevertheless, while gamification benefits others, few students still perceive self-study and lectures as more critical in their learning experience.Theory and Practical Implications – Specific designed game can be a valuable tool for students to learn accounting which in this study includes accounting terms and concepts. Nevertheless, educators interested in applying gamification in the classroom need reasonable anticipation and proper preparation. Novelty – This study contributes to the literature on gamification in accounting education which currently is limited.